Nutrition of School-Aged Children and Adolescents in Europe and Central Asia Region: A Literature and Survey Review. Issue 1 (March 2023) - Mates, Emily; Lelijveld, Natasha; Ali, Zakari; Sadler, Kate; Yarparvar, Amirhossein; Walters, Tamsin; Brown, Rebecca; Rodriques, Basil
Background: Middle childhood and adolescence are critical times for the growth, development, and establishment of healthy eating habits. The Europe and Central Asia (ECA) region has been through economic and nutrition transitions over the past 20 years, which are likely to have affected the nutritional status of this group. Objective: This review aimed to collate data on the nutritional status and dietary patterns of school-aged children (SAC) and adolescents (5-19 years) across the ECA region in order to inform policy and programming decisions. Methods: A systematic search of the literature in Pubmed, Cochrane, and ScienceDirect databases was conducted (April 2019), complemented by a systematic review of nationally representative surveys. Inclusion criteria were any data on micronutrient deficiencies, overweight, stunting, wasting, thinness, or dietary patterns in SAC and adolescents in the 21 UNICEF-defined countries of ECA, published since the year 2000. Results: Results included 134 published papers and 6 sources of survey data. The majority of studies were conducted in Turkey (56%), with all other countries having fewer than 10 studies each; 8 countries in the region having no studies on this age group at all. The most significant nutrition issue was overweight and obesity. Micronutrient deficiencies, particularly anemia, emerge as a further challenge. Dietary patterns were worse in urban areas and boys. Conclusions: The findings of this review suggest that there are 3 critical areas that need immediate attention: the promotion of healthy diets and physical activity to address high levels of overweight/obesity, anemia prevention efforts, and addressing the considerable data gaps for SAC and adolescent nutrition.